Gadolinium element doped zinc oxide coated positive electrode material and preparation method and application thereof

Through the preparation method of the positive electrode material coated with zinc oxide doped with gadolinium, the problems of complex preparation process and poor conductivity of polyanionic compounds are solved, and the high capacity and high circulation performance are improved, and the reaction with the electrolyte is avoided, saving energy consumption.

CN119240646APending Publication Date: 2025-01-03GEM WUXI ENERGY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411371480.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The preparation process of the existing polyanionic compound Na4Fe3(PO4)2P2O7 is complicated, with poor heterophasic and intrinsic electron conductivity, which is easy to react with the electrolyte, resulting in a decrease in capacity and poor cycle stability.

Method used

The preparation method of the positive electrode material coated with gadolinium element doped with zinc oxide is used. Solid gel method is used to mix sodium, gadolinium, iron and carbon sources, and zinc oxide is coated in the protective gas after sintering to control the low sintering temperature. At 600°C, excellent discharge specific capacity and cycling performance were formed.

Benefits of technology

The inherent electronic conductivity of the positive electrode material is improved, the diffusion energy barrier of sodium ions is reduced, the reaction with the electrolyte is avoided, the capacity and circulation performance are improved, and energy consumption is saved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005067690190000081
    Figure BDA0005067690190000081
Patent Text Reader

Abstract

The invention belongs to the technical field of positive electrode materials, and particularly relates to a gadolinium element doped zinc oxide coated positive electrode material and a preparation method and application thereof. The invention provides a preparation method of a gadolinium-doped zinc oxide-coated positive electrode material, which comprises the following steps: (1) mixing a sodium source, a gadolinium source, an iron source and a carbon source, and preparing a precursor by adopting a sol-gel method; (2) mixing the precursor with zinc oxide, and sintering; the sintering temperature is not higher than 600 DEG C. The positive electrode material prepared by the invention is a polyanionic compound (NFPP), is not easy to react with electrolyte, and is large in capacity and good in cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of positive electrode materials, and in particular relates to a positive electrode material coated with gadolinium-doped zinc oxide, and a preparation method and application thereof. Background Art

[0002] At present, electrochemical energy storage technology is deepening its research direction towards high energy density, rapid response capability and flexible adaptability. Sodium-ion batteries have attracted attention due to the widespread distribution of sodium resources around the world and their low cost. However, the reaction kinetics of sodium ions themselves are sluggish, and how to improve their capacity and durability has become a major difficulty. Polyanionic compounds are often considered as positive electrode materials for sodium-ion batteries due to their good long-term cycle stability and rate performance.

[0003] Among them, the polyanionic compound Na4Fe3(PO4)2P2O7 has a solid crystal framework and an open three-dimensional Na + Diffusion channel, but the compound has a complex structure and requires strict control of synthesis conditions. At the same time, the obtained Na4Fe3(PO4)2P2O7 has disadvantages such as impurities and poor intrinsic electronic conductivity. The obtained positive electrode material is also easy to react with the electrolyte, resulting in a decrease in capacity and poor cycle stability. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the prior art in that the process for preparing polyanionic compounds is complicated, the prepared positive electrode materials have impurities, poor intrinsic electronic conductivity, are easy to react with the electrolyte, resulting in decreased capacity, poor cycle stability, etc., thereby providing a positive electrode material coated with gadolinium doped zinc oxide, and a preparation method and application thereof.

[0005] To this end, the present invention provides the following technical solutions.

[0006] The present invention provides a method for preparing a positive electrode material coated with gadolinium-doped zinc oxide, comprising the following steps:

[0007] (1) mixing a sodium source, a gadolinium source, an iron source and a carbon source, and preparing a precursor by a sol-gel method;

[0008] (2) Mixing the precursor and zinc oxide and sintering; the sintering temperature is not higher than 600° C.

[0009] The precursor is a polyanionic compound;

[0010] The specific steps of the step (1) of the sol-gel method include: stirring the mixed solution at 50-100° C. for 5-15 hours to obtain a precursor;

[0011] In an optional embodiment, in step (2), the mixing comprises ball milling mixing;

[0012] In an optional embodiment, the sintering includes a first sintering and a second sintering;

[0013] Preferably, the second sintering temperature is not higher than 600°C.

[0014] In an optional embodiment, the temperature of the first sintering is 300-400°C;

[0015] In an optional embodiment, the first sintering time is 2-8h;

[0016] In an optional embodiment, the second sintering temperature is 400-600°C;

[0017] In an optional embodiment, the second sintering time is 5-15 hours.

[0018] In an optional embodiment, the heating rate of the first sintering is 2-5°C / min;

[0019] In an optional embodiment, the heating rate of the second sintering is 2-5°C / min;

[0020] In an optional embodiment, the molar ratio of the sodium source, the gadolinium source and the iron source is (1-5):(0-0.7):(1-3); wherein the molar amount of the gadolinium source is not 0;

[0021] In an optional embodiment, the mass ratio of the precursor to zinc oxide is 1:(0-0.01), wherein the mass of zinc oxide is not 0;

[0022] In an optional embodiment, the molar ratio of the sodium element in the sodium source to the carbon source is (1-5):(2-5).

[0023] In an optional embodiment, the sodium source includes at least one of sodium dihydrogen phosphate, sodium bicarbonate and sodium carbonate;

[0024] In an optional embodiment, the gadolinium source includes at least one of gadolinium nitrate and gadolinium chloride;

[0025] In an optional embodiment, the iron source includes at least one of ferrous oxalate, ferric phosphate and ferric nitrate;

[0026] In an alternative embodiment, the carbon source includes at least one of citric acid and glucose.

[0027] When mixed with the sodium source, the gadolinium source and the iron source, the carbon source is added in the form of a solution, the concentration of the carbon source in the solution is not higher than 0.1 mol / L, and the solvent in the solution is a common solvent in the art, such as at least one of water and ethanol;

[0028] In an optional embodiment, the sintering is performed under protective gas.

[0029] In an optional embodiment, the protective gas includes at least one of argon and nitrogen.

[0030] In an optional embodiment, the sintering further includes introducing protective gas for 30-60 minutes;

[0031] In an optional embodiment, during the sintering, the flow rate of the protective gas is 10-100 mL / min.

[0032] The present invention provides a positive electrode material coated with gadolinium-doped zinc oxide;

[0033] Preferably, the mass fraction of the zinc oxide coating layer to the gadolinium-doped zinc oxide-coated positive electrode material is 0-1%; wherein the mass of the zinc oxide coating layer is not 0.

[0034] The present invention provides a positive electrode material coated with gadolinium-doped zinc oxide prepared by the above preparation method or the use of the positive electrode material coated with gadolinium-doped zinc oxide in a sodium ion battery or a positive electrode sheet of a sodium ion battery.

[0035] The technical solution of the present invention has the following advantages:

[0036] 1. The preparation method of the positive electrode material coated with gadolinium-doped zinc oxide provided by the present invention comprises: (1) mixing a sodium source, a gadolinium source, an iron source and a carbon source, and preparing a precursor by a sol-gel method; (2) mixing the precursor with zinc oxide and sintering; the sintering temperature is not higher than 600°C. The polyanion positive electrode material prepared by the present invention has excellent discharge specific capacity and cycle performance. Specifically, the present invention adds gadolinium doping, which reduces the band gap of the polyanion compound and improves the inherent electronic conductivity of the positive electrode material; wherein, Gd 3+ The ionic radius is larger than that of Fe 2+, which expands the lattice structure of the positive electrode material, reduces the energy barrier for sodium ion diffusion, improves electronic conductivity, and increases the capacity of the positive electrode material. The present invention uses zinc oxide to coat the positive electrode material, which can effectively isolate the positive electrode material from contact with the electrolyte, avoid the positive electrode material and the electrolyte from contacting and reacting during the charge and discharge process, and further improve the cycle performance of the material. When the sintering temperature is higher than 600°C, the obtained material will form an impure phase, reducing the capacity and stability of the material; and the present invention greatly saves energy consumption. The present invention dopes gadolinium into the polyanionic compound positive electrode material and introduces a zinc oxide coating layer to enable the positive electrode material to have both high capacity and high cycle performance.

[0037] 2. The preparation method of the positive electrode material coated with gadolinium doped zinc oxide provided by the present invention, the precursor is prepared by the sol-gel method, and the components can be fully mixed to avoid uneven components of the prepared positive electrode material, thereby reducing its capacity and cycle performance. The molar ratio of the sodium source, gadolinium source and iron source is (1-5): (0-0.7): (1-3); wherein the molar amount of the gadolinium source is not 0; the molar ratio of the sodium source, gadolinium source and iron source described in the present invention can effectively reduce the Na2FeP2O7 and NaFePO4 impurities, thereby improving the purity of the prepared material; the impurities will reduce the capacity and stability of the material; if the gadolinium source is selected to be 0, the conductive performance of the material will be reduced, and excessive addition of the gadolinium source will destroy the generated NFPP phase structure and reduce the capacity. The mass ratio of the precursor to zinc oxide is 1:(0-0.01), wherein the mass of zinc oxide is not 0; excessive addition of zinc oxide will block the active sites on the surface of the material and reduce conductivity; failure to add zinc oxide will cause the positive electrode material to contact the electrolyte, thereby reducing capacity and stability.

[0038] 3. The preparation method of the positive electrode material coated with gadolinium-doped zinc oxide provided by the present invention, the temperature of the second sintering is 400-600°C, and sintering in this temperature range can form a polyanionic compound (NFPP), further improving the capacity and cycle performance of the prepared material. DETAILED DESCRIPTION

[0039] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0040] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0041] Example 1

[0042] This embodiment provides a method for preparing a positive electrode material coated with gadolinium-doped zinc oxide, comprising the following steps:

[0043] (1) NaH2PO4, Gd(NO3)3·6H2O and FeC2O4·2H2O were dissolved in a citric acid solution (the solvent was water and ethanol, and the volume ratio of water to ethanol was 10:1) at a molar ratio of 3.4:0.3:2.4, and stirred at 80°C for 12 hours to prepare a precursor; wherein the molar ratio of NaH2PO4 to citric acid was 2:3; and the concentration of the citric acid solution was 0.03 mol / L;

[0044] (2) The precursor and zinc oxide were ball-milled and mixed, the mass ratio of the precursor to zinc oxide was 1:0.006, argon was introduced for 50 min, the mixed powder was heated to 350° C. at 2° C. / min for pretreatment for 5 h, and the temperature was increased at 2° C. / min under an argon atmosphere and sintered at 550° C. for 12 h to obtain a gadolinium-doped zinc oxide-coated positive electrode material, the flow rate of the argon was 50 mL / min.

[0045] Example 2

[0046] This embodiment provides a method for preparing a positive electrode material coated with gadolinium-doped zinc oxide. Compared with Example 1, the difference is that, in step (1), the NaH2PO4, Gd(NO3)3·6H2O and FeC2O4·2H2O are dissolved in a citric acid solution at a molar ratio of 3.4:0.1:2.4 instead of NaH2PO4, Gd(NO3)3·6H2O and FeC2O4·2H2O being dissolved in a citric acid solution at a molar ratio of 3.4:0.3:2.4.

[0047] Example 3

[0048] This embodiment provides a method for preparing a positive electrode material coated with gadolinium-doped zinc oxide. Compared with Example 1, the difference is that, in step (1), the NaH2PO4, Gd(NO3)3·6H2O and FeC2O4·2H2O are dissolved in a citric acid solution at a molar ratio of 3.4:0.5:2.4 instead of NaH2PO4, Gd(NO3)3·6H2O and FeC2O4·2H2O being dissolved in a citric acid solution at a molar ratio of 3.4:0.3:2.4.

[0049] Example 4

[0050] This embodiment provides a method for preparing a positive electrode material coated with gadolinium-doped zinc oxide. Compared with Embodiment 1, the difference is that, in step (1), the NaH2PO4, Gd(NO3)3·6H2O and FeC2O4·2H2O are dissolved in a citric acid solution at a molar ratio of 3.4:0.7:2.4 instead of NaH2PO4, Gd(NO3)3·6H2O and FeC2O4·2H2O being dissolved in a citric acid solution at a molar ratio of 3.4:0.3:2.4.

[0051] Example 5

[0052] This embodiment provides a method for preparing a positive electrode material coated with gadolinium-doped zinc oxide, comprising the following steps:

[0053] (1) Sodium carbonate, Gd(NO3)3·6H2O and ferric nitrate were dissolved in a glucose solution (the solvent was water and ethanol, and the volume ratio of water to ethanol was 7:1) at a molar ratio of 3.4:0.3:1.5, and stirred at 60°C for 6 hours to prepare a precursor; wherein the molar ratio of sodium carbonate to glucose was 2:5; and the concentration of the glucose solution was 0.07 mol / L;

[0054] (2) The precursor and zinc oxide were ball-milled and mixed, the mass ratio of the precursor to zinc oxide was 1:0.01, argon was introduced for 50 min, the mixed powder was heated to 400 ° C at 2 ° C / min for pretreatment for 8 h, and the temperature was increased at 2 ° C / min in an argon atmosphere at 600 ° C for 7 h to obtain a gadolinium-doped zinc oxide-coated positive electrode material, the flow rate of the argon was 90 mL / min.

[0055] Comparative Example 1

[0056] This comparative example provides a method for preparing a positive electrode material coated with gadolinium-doped zinc oxide. Compared with Example 1, the difference is that in step (1), Gd(NO3)3·6H2O is not added; in step (2), zinc oxide is not added.

[0057] Comparative Example 2

[0058] This comparative example provides a method for preparing a positive electrode material coated with gadolinium-doped zinc oxide. Compared with Example 1, the difference is that in step (1), Gd(NO3)3·6H2O is not added.

[0059] Comparative Example 3

[0060] This comparative example provides a method for preparing a positive electrode material coated with gadolinium-doped zinc oxide. Compared with Example 1, the difference is that in step (2), zinc oxide is not added.

[0061] Comparative Example 4

[0062] This comparative example provides a method for preparing a positive electrode material coated with gadolinium-doped zinc oxide. Compared with Example 1, the difference is that in step (1), Ce(NO3)3 is used to replace Gd(NO3)3·6H2O in an equimolar manner.

[0063] Comparative Example 5

[0064] This comparative example provides a method for preparing a positive electrode material coated with gadolinium-doped zinc oxide. Compared with Example 1, the difference is that the sintering temperature is 700° C. instead of 550° C. in Example 1.

[0065] Test Case

[0066] This test example provides the performance test of the positive electrode materials of each embodiment and comparative example, as follows:

[0067] Assemble the battery: weigh the positive electrode material, acetylene black and PVDF in a mass ratio of 80:12:8, add the solvent NMP and ball mill for 1 hour to prepare the positive electrode slurry, evenly coat it on the aluminum foil, dry it, and press it into the positive electrode sheet; use the metal sodium sheet as the counter electrode, the glass fiber as the diaphragm, and the 1 mol / L NaClO4 (solvent is PC) solution as the electrolyte, and package it into a CR2032 button battery under argon atmosphere.

[0068] (1) 0.1C first discharge measurement: At room temperature, in a blue power test system, with a cut-off voltage of 2.0-4.0V, the battery was charged once at 0.1C and discharged once at 0.1C. The results are shown in Table 1.

[0069] (2) Cycle performance test method: The battery was charged at 0.1C and discharged at 0.1C for 50 cycles, and the cycle performance was calculated. The results are shown in Table 1.

[0070] Table 1 Performance of batteries made of positive electrode materials obtained in various embodiments and comparative examples

[0071]

[0072] As shown in Table 1, after the positive electrode material of the present invention doped with gadolinium element and coated with zinc oxide is made into a battery, the 0.1C first discharge is greater than 104.8 mAh / g, and the capacity retention rate after 50 cycles is maintained at about 90.6% of the initial discharge capacity.

[0073] In Comparative Example 1, gadolinium nitrate and zinc oxide are not added, and its 0.1C discharge capacity and cycle performance are greatly reduced, indicating that the performance of the obtained material can be greatly improved by doping gadolinium and coating zinc oxide on the surface of the present invention; in Comparative Example 2, gadolinium nitrate is not added, and its 0.1C discharge capacity and cycle performance are worse than those of the embodiment; in Comparative Example 3, zinc oxide coating is not added, and the 0.1C discharge capacity is affected, but the effect is not significant, and after 50 cycles, the cycle performance is greatly reduced; indicating that the prepared positive electrode material reacts with the electrolyte during the charge and discharge process, reducing the cycle performance. In Comparative Example 4, cerium is used instead of gadolinium doping, and the capacity and cycle performance of the prepared positive electrode material are reduced, indicating that gadolinium doping can effectively improve the capacity and cycle performance of the material. Comparative Example 5 shows that the positive electrode material prepared at a sintering temperature greater than 600°C will generate impurities, the capacity will decrease, and the cycle performance will deteriorate.

[0074] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing a positive electrode material coated with gadolinium-doped zinc oxide, characterized in that: The steps include: (1) mixing a sodium source, a gadolinium source, an iron source and a carbon source, and preparing a precursor by a sol-gel method; (2) Mixing the precursor and zinc oxide and sintering; the sintering temperature is not higher than 600° C.

2. The preparation method according to claim 1, characterized in that: The sintering includes a first sintering and a second sintering; Preferably, the second sintering temperature is not higher than 600°C.

3. The preparation method according to claim 2, characterized in that: The first sintering temperature is 300-400° C.; and / or, The first sintering time is 2-8 hours; and / or, The second sintering temperature is 400-600° C.; and / or, The second sintering time is 5-15h.

4. The preparation method according to claim 1, characterized in that: The molar ratio of the sodium source, the gadolinium source and the iron source is (1-5):(0-0.7):(1-3); wherein the molar amount of the gadolinium source is not 0; and / or, The mass ratio of the precursor to zinc oxide is 1:(0-0.01), wherein the mass of zinc oxide is not 0; and / or, The molar ratio of the sodium element in the sodium source to the carbon source is (1-5):(2-5).

5. The preparation method according to claim 4, characterized in that: The sodium source comprises at least one of sodium dihydrogen phosphate, sodium bicarbonate and sodium carbonate; and / or, The gadolinium source comprises at least one of gadolinium nitrate and gadolinium chloride; and / or, The iron source comprises at least one of ferrous oxalate, ferric phosphate and ferric nitrate; and / or, The carbon source includes at least one of citric acid and glucose.

6. The preparation method according to claim 1, characterized in that: The sintering is performed under protective gas.

7. The preparation method according to claim 6, characterized in that: The protective gas includes at least one of argon and nitrogen.

8. The preparation method according to claim 6, characterized in that: The sintering step also includes introducing protective gas for 30-60 minutes before sintering; and / or, During the sintering, the flow rate of the protective gas is 10-100 mL / min.

9. A positive electrode material coated with gadolinium-doped zinc oxide; Preferably, the mass fraction of the zinc oxide coating layer in the positive electrode material coated with gadolinium-doped zinc oxide is 0-1%; wherein, The mass of the zinc oxide coating is not zero.

10. Use of the positive electrode material coated with gadolinium-doped zinc oxide prepared by the preparation method according to any one of claims 1 to 8 or the positive electrode material coated with gadolinium-doped zinc oxide according to claim 9 in a sodium ion battery or a positive electrode sheet of a sodium ion battery.